The effect of signposts on access speed and lookup task success in long and short entries - Lew, Robert; Pajkowska, Julita (Horizontes de Lingüística Aplicada, 2007)
One difficulty in using dictionaries is recognizing the relevant sense in polysemous entries. With a view to assisting dictionary users on this point, recent editions of some learners’ dictionaries have introduced sense access facilitating devices into longer entries. The present study attempts to verify experimentally the effectiveness of one such device.
Keywords: Dictionaries; Dictionary access; Sense discrimination; Language learners